Wider die professionelle Gedächtnislücke. - (:unkn) unknown (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
The european Network of Landscape Architecture Archives NELA was founded in 2019 and counts eight members to date. Neither the landscape nor the professional occupation ends at national borders; people, works, theories, styles and challenges are international. Beyond unravelling those connections NELA aims at an exchange and mutual support as well as joint research and publication projects on the history of our profession, which will serve as a basis for further development.
Filling the gaps in the profession´s memory NELA – Network of European Landscape Architecture Archives.
Keywords: Landschaftsarchitektur; Archiv; Forschung; Fachgebiet; Netzwerk; Internationale Zusammenarbeit; Vernetzung